2023
DOI: 10.1158/1535-7163.mct-21-0880
|View full text |Cite
|
Sign up to set email alerts
|

Small-Molecule–Mediated Stabilization of PP2A Modulates the Homologous Recombination Pathway and Potentiates DNA Damage-Induced Cell Death

Abstract: High-Grade Serous Carcinoma (HGSC) is the most common and lethal ovarian cancer subtype. PARP-inhibitors (PARPi) have become the mainstay of HGSC targeted therapy, given that these tumors are driven by a high degree of genomic instability and Homologous Recombination (HR) defects. Nonetheless, ~30% of patients initially respond to treatment, ultimately relapsing with resistant disease. Thus, despite recent advances in drug development and an increased understanding of genetic alterations driving HGSC progressi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 65 publications
1
5
2
Order By: Relevance
“…Catalytic inhibition of PP2A-like phosphatases by LB-100, as well as loss of specific PP2A B-type subunits, Aα subunit or activator PTPA, have all been shown to inhibit HR and sensitize cells for DSBs (Ambjørn et al, 2021; Aouida et al, 2019; Kalev et al, 2012; Wei et al, 2013). As our data also suggested decreased repair and radiosensitization upon TIPRL1 depletion, this does again not seem to align well with a phosphatase inhibitory role of TIPRL1, although a recent publication demonstrated sensitization to PARP inhibitors by PP2A activating compounds (SMAPs) via a decrease in HR that was found dependent on RAD51 dysregulation (Avelar et al, 2023). Finally, the contribution of TIPRL1 to DSB repair may also involve its modulation of PP4 (Feng et al, 2016; Gingras et al, 2005), which has been shown to dephosphorylate a large number of DDR regulators (e.g.…”
Section: Discussioncontrasting
confidence: 75%
“…Catalytic inhibition of PP2A-like phosphatases by LB-100, as well as loss of specific PP2A B-type subunits, Aα subunit or activator PTPA, have all been shown to inhibit HR and sensitize cells for DSBs (Ambjørn et al, 2021; Aouida et al, 2019; Kalev et al, 2012; Wei et al, 2013). As our data also suggested decreased repair and radiosensitization upon TIPRL1 depletion, this does again not seem to align well with a phosphatase inhibitory role of TIPRL1, although a recent publication demonstrated sensitization to PARP inhibitors by PP2A activating compounds (SMAPs) via a decrease in HR that was found dependent on RAD51 dysregulation (Avelar et al, 2023). Finally, the contribution of TIPRL1 to DSB repair may also involve its modulation of PP4 (Feng et al, 2016; Gingras et al, 2005), which has been shown to dephosphorylate a large number of DDR regulators (e.g.…”
Section: Discussioncontrasting
confidence: 75%
“…Protein phosphatase 2A (PP2A), a serine/threonine phosphatase, is known to regulate key cellular functions such as cell growth, metabolism, and apoptosis (19). We recently identified a small-molecule activator of PP2A (SMAP) (20,21), and we and others demonstrated that PP2A reactivation is a therapeutically viable strategy in various cancer models (22)(23)(24)(25)(26)(27)(28)(29). Similar findings have been reported by modulating endogenous PP2A inhibitors such as CIP2A or SET (30).…”
Section: Introductionsupporting
confidence: 71%
“…We recently published on a series of first-in-class SMAPs (20,21). We and others previously reported that PP2A activation is a viable therapeutic strategy against cancer (22)(23)(24)(25)(26)(27)(28)(29). In one of the protein Bim to Mcl-1, Bcl-xL, and Bcl-2 following incubation with BH domain antagonists (VEN, S63845, or A1155463) in agonist mixtreated primary CLL cells that exhibited overexpression of antiapoptotic proteins and multidrug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…To assess whether this association was also observed with PARPi, two isogenic OvCa cell line pairs (OV81.2 and OV231) were analyzed. The two OvCa cell line pairs were generated through platinum-drug selection and became cisplatin and PARPi resistant [ 25 , 26 ]. We found that the miR-181a levels were significantly increased in cisplatin- and PARPi-resistance cell lines compared to corresponding parental cell lines (Fig.…”
Section: Resultsmentioning
confidence: 99%